2009
DOI: 10.1051/0004-6361/200811038
|View full text |Cite
|
Sign up to set email alerts
|

Sub-hour modulation of non-Io Jovian decametric emission

Abstract: The variability of Jovian decametric emission (DAM), which is not controlled by the Io satellite (non-Io), was studied of timescales of between 1 min and 1 h with DAM records of 1991-2007 from the archive of Nançay Radio Observatory. We found that the internal structure of the non-Io radio storms has the dominating periodicity on of average 21 ± 2 min . This estimate is in close agreement with the periodicity of Io-related emission and with fundamental eigenoscillations of transversal magnetic pulsations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…Properties of the 4.75 GHz radio emission from J1047+21 are broadly similar to those observed in bursts from other ultracool dwarfs (Berger et al 2001;Hallinan et al 2007Hallinan et al , 2008Berger et al 2009;McLean et al 2011), the Sun (Chernov 2006;White 2007), and the solar system planets (Arkhypov & Rucker 2009;Lamy et al 2010;Mutel et al 2010). A closer examination of sufficiently high signal-to-noise sections of the first two bursts reveals spikes that last no longer than ∼0.5 s. The presence of rapid intensity fluctuations in the data suggests that the shortest observable timescales of these variations may be limited by our 0.1s sampling.…”
Section: Characteristics Of J1047+21supporting
confidence: 52%
“…Properties of the 4.75 GHz radio emission from J1047+21 are broadly similar to those observed in bursts from other ultracool dwarfs (Berger et al 2001;Hallinan et al 2007Hallinan et al , 2008Berger et al 2009;McLean et al 2011), the Sun (Chernov 2006;White 2007), and the solar system planets (Arkhypov & Rucker 2009;Lamy et al 2010;Mutel et al 2010). A closer examination of sufficiently high signal-to-noise sections of the first two bursts reveals spikes that last no longer than ∼0.5 s. The presence of rapid intensity fluctuations in the data suggests that the shortest observable timescales of these variations may be limited by our 0.1s sampling.…”
Section: Characteristics Of J1047+21supporting
confidence: 52%
“…However, there are studies which suggest also the low-latitude (L < 6) sources. Arkhypov and Rucker [2009] have shown that the periodicity of the non-Io storms coincide with the fundamental eigenmode of the Io torus oscillation and therefore part of the non-Io emission can be directly related to the plasma torus. Therefore one possible source candidate for the energetic particles which may produce the periodic burst of non-Io DAM is the Io plasma torus which consists of highly structured plasma regions.…”
Section: Discussionmentioning
confidence: 96%
“…However there are several studies which indicate also the existence of a low-latitude (L < 6) component of the non-Io emission, possibly related to the Io torus. Arkhypov and Rucker [2009] have shown that the periodicity of the non-Io storms coincide with the fundamental eigenmode of the Io torus oscillation and therefore part of the non-Io emission can be directly related to the plasma torus.…”
Section: Discussionmentioning
confidence: 96%